Blood–Brain Barrier Permeability Is Associated With Cognitive Functioning in Normal Aging and Neurodegenerative Diseases - Danielle C. Hergert; Owen Gaasedelen; Sephira G. Ryman; Jillian Prestopnik; Arvind Caprihan; Gary A. Rosenberg (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The purpose of this study was to investigate the relationship between blood–brain barrier (BBB) permeability and cognitive functioning in healthy older adults and individuals with neurodegenerative diseases. Methods and Results A total of 124 participants with Alzheimer disease, cerebrovascular disease, or a mix Alzheimer's and cerebrovascular diseases and 55 controlparticipants underwent magnetic resonance imaging and neuropsychological testing. BBB permeability was measured with dynamic contrast‐enhanced magnetic resonance imaging and white matter injury was measured using a quantitative diffusion‐tensor imaging marker of white matter injury. Structural equation modeling was used to examine the relationships between BBB permeability, vascular risk burden, white matter injury, and cognitive functioning. Vascular risk burden predicted BBB permeability (r=0.24, P<0.05) and white matter injury (r=0.38, P<0.001). BBB permeability predicted increased white matter injury (r=0.34, P<0.001) and increased white matter injury predicted lower cognitive functioning (r=−0.51, P<0.001). Conclusions The study provides empirical support for a vascular contribution to white matter injury and cognitive impairment, directly or indirectly via BBB permeability. This highlights the importance of targeting modifiable vascular risk factors to help mitigate future cognitive decline.